Catalyst for synthesizing methanol by hydrogenation of carbon dioxide, preparation method and use thereof, and method for synthesizing methanol by hydrogenation of carbon dioxide

By developing the spinel-structured nanoparticle catalyst xM-ZnFe2O4, the problem of unstable activity of traditional Cu-based catalysts under high temperature and high pressure conditions was solved, and efficient CO2 conversion and methanol yield were achieved.

CN116474779BActive Publication Date: 2025-03-18SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211663851.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-03-18
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

Traditional Cu-based catalysts have poor water resistance under high temperature and high pressure conditions, and are prone to sintering of active sites, resulting in unstable catalytic activity, and the catalyst's conversion efficiency to CO2 is low, making it difficult to maintain long-term stability.

Method used

A spinel structure nanoparticle catalyst xM-ZnFe2O4 is developed. The M element is selected from at least one of In, Pd, Pt, Cu, Cr, Ga, and Zr. It is prepared by drying and calcining, with an average particle size of 10-15 nm.

Benefits of technology

The catalyst operates stably under high temperature conditions and has high methanol selectivity. It can effectively promote the adsorption and activation of CO2 and H2, and improve CO2 conversion and methanol yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0004013897220000011
    Figure HDA0004013897220000011
  • Figure HDA0004013897220000012
    Figure HDA0004013897220000012
Patent Text Reader

Abstract

The present invention provides a catalyst for synthesizing methanol by hydrogenation of carbon dioxide, a preparation method and use thereof, and a method for synthesizing methanol by hydrogenation of carbon dioxide. The general formula of the catalyst is xM-ZnFe2O4, the M element is selected from at least one of In, Pd, Pt, Cu, Cr, Ga, and Zr, and the content of the M element is x=0-5wt%, and has a spinel structure. The preparation method comprises drying and roasting a mixed solution comprising zinc salt, iron salt, optional salt of the M element, an organic solvent, and water. The catalyst is used for synthesizing methanol by hydrogenation of carbon dioxide. The method for synthesizing methanol by hydrogenation of carbon dioxide comprises reacting a raw gas containing CO2 and H2 under the catalyst conditions. The catalyst of the present invention operates stably under high temperature conditions above 280°C, and has a high methanol selectivity. The adsorption activation of CO2 and H2 is promoted by doping with the M element, and the CO2 conversion rate and the methanol space-time yield are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a catalyst for synthesizing methanol by hydrogenating carbon dioxide, a preparation method and use thereof, and a method for synthesizing methanol by hydrogenating carbon dioxide. Background Art

[0002] CO 2 Converting it into high-value-added chemicals and fuels can not only solve the problem of excessive CO 2 It can not only solve environmental problems such as global warming caused by carbon dioxide emissions, but also effectively alleviate the problem of excessive dependence on fossil fuels. Among them, methanol, as an ideal low-carbon clean fuel, can replace oil and gas, which helps to solve the problem of carbon emissions in transportation; as an intermediate, it is widely used in basic industries such as chemical industry and material synthesis, which can promote green manufacturing; as an excellent hydrogen storage material, it can alleviate the problems of hydrogen energy storage and transportation safety and cost. Therefore, green hydrogen produced by renewable energy can convert CO 2 Converting it into high value-added methanol can not only solve the problem of energy storage and transportation, but also neutralize CO 2 , realizing the recycling of carbon.

[0003] Among them, Cu-based catalysts are the most widely used, which is attributed to their high reaction activity and methanol space-time yield. However, the poor water resistance of traditional Cu-based catalysts leads to easy sintering of active sites, which seriously affects the stability of their catalytic activity. 2 The core part of the hydrogenation reaction system still has some problems, such as the catalyst itself for CO 2 The catalytic conversion efficiency is low, and it is difficult to maintain long-term stability under high temperature and high pressure reaction conditions; some existing catalyst raw materials are expensive, and the preparation process is cumbersome and time-consuming. Therefore, it is of great significance to develop a catalyst for the hydrogenation of carbon dioxide to methanol with strong stability, good methanol selectivity, simple preparation process and low cost. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a catalyst for synthesizing methanol by hydrogenating carbon dioxide, a preparation method and use thereof, and a method for synthesizing methanol by hydrogenating carbon dioxide.

[0005] To achieve the above-mentioned and other related purposes, the present invention provides a catalyst for synthesizing methanol by hydrogenation of carbon dioxide in a first aspect, wherein the general formula of the catalyst is xM-ZnFe 2 O 4, the M element is selected from at least one of In, Pd, Pt, Cu, Cr, Ga, and Zr, the content of the M element x is 0 to 5wt%, such as 0 to 1wt%, 1 to 2wt%, 2 to 3wt%, 3 to 4wt% or 4 to 5wt%, and the catalyst has a spinel structure.

[0006] x is the mass of M element as a percentage of M element and ZnFe 2 O 4 The percentage of the total mass. The M element exists in the catalyst in the form of oxide.

[0007] Preferably, the catalyst is nanoparticles with an average particle size of 10 to 15 nm.

[0008] The second aspect of the present invention provides a method for preparing the above catalyst, wherein a mixed solution including zinc salt, iron salt, optional salt of element M, organic solvent and water is dried and calcined to obtain the catalyst.

[0009] Preferably, the zinc salt is selected from at least one of zinc nitrate, zinc acetate and zinc chloride;

[0010] And / or, the iron salt is selected from at least one of ferric nitrate, ferric chloride and ferric citrate;

[0011] And / or, the salt of element M is selected from at least one of nitrate of element M and chloride of element M;

[0012] And / or, the organic solvent is selected from at least one of urea, citric acid, oxalic acid and sucrose.

[0013] Preferably, the molar ratio of the zinc salt, the iron salt and the organic solvent is 1:2:3-6, such as the molar ratio of the zinc salt to the organic solvent is 1:3-4.5 or 1:4.5-6;

[0014] And / or, the content of the M element is 0-5wt%, such as 0-1wt%, 1-2wt%, 2-3wt%, 3-4wt% or 4-5wt%;

[0015] and / or, the drying temperature is 80-120°C, such as 80-90°C, 90-100°C, 100-110°C or 110-120°C;

[0016] and / or, the drying time is 2 to 4 hours;

[0017] and / or, the calcination temperature is 350-430° C., such as 350-400° C. or 400-430° C.;

[0018] And / or, the calcination time is 4 to 8 hours, such as 4 to 6 hours or 6 to 8 hours.

[0019] The third aspect of the present invention provides the use of the above catalyst for synthesizing methanol by hydrogenation of carbon dioxide.

[0020] Preferably, CO 2 and H 2 The raw material gas is reacted under the catalyst conditions to obtain methanol.

[0021] More preferably, H 2 With CO 2 The molar ratio is 2 to 4, such as 2 to 3 or 3 to 4;

[0022] And / or, the mass space velocity of the reaction is 2000~20000mL / g cat / h, such as 2000~9000mL / g cat / h、9000~15000mL / g cat / h、15000~18000mL / g cat / h or 18000~20000mL / g cat / h;

[0023] And / or, the reaction pressure is 3-5 MPa, such as 3-4 MPa or 4-5 MPa;

[0024] and / or, the reaction temperature is 280-340°C, such as 280-290°C, 290-300°C, 300-310°C, 310-320°C, 320-330°C or 330-340°C;

[0025] And / or, the reaction is carried out in a fixed bed reactor.

[0026] A fourth aspect of the present invention provides a method for synthesizing methanol by hydrogenating carbon dioxide, comprising: 2 and H 2 The raw material gas reacts under the above-mentioned catalyst conditions to obtain methanol.

[0027] Preferably, H 2 With CO 2 The molar ratio is 2 to 4, such as 2 to 3 or 3 to 4;

[0028] And / or, the mass space velocity of the reaction is 2000~20000mL / g cat / h, such as 2000~9000mL / g cat / h、9000~15000mL / g cat / h、15000~18000mL / g cat / h or 18000~20000mL / g cat / h;

[0029] And / or, the reaction pressure is 3-5 MPa, such as 3-4 MPa or 4-5 MPa;

[0030] And / or, the reaction temperature is 280-340°C, such as 280-290°C, 290-300°C, 300-310°C, 310-320°C, 320-330°C or 330-340°C.

[0031] And / or, the reaction is carried out in a fixed bed reactor.

[0032] As described above, the present invention has at least one of the following beneficial effects:

[0033] 1) The catalyst of the present invention is a nanoparticle with a spinel structure, and the average particle size thereof is 10 to 15 nm.

[0034] 2) The preparation method of the catalyst of the present invention adopts an organic combustion method, and the preparation process is short, which greatly saves the time cost and economic cost of preparing the catalyst and is conducive to industrial scale-up production.

[0035] 3) The catalyst of the present invention can operate stably under high temperature conditions and has a high methanol selectivity. The xM-ZnFe 2 O 4 , which can promote CO 2 and H 2 The adsorption and activation of CO 2 Conversion rate and methanol space-time yield.

[0036] 4) The catalyst of the present invention operates stably under high temperature conditions above 280°C and has a high methanol selectivity (up to 87.6%). The CO selectivity can be further improved by doping with M metal elements. 2 Conversion rate and methanol yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the XRD spectrum of the product in Example 1.

[0038] Figure 2 This is the TEM image of the product in Example 1. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention, but not to limit the scope of the present invention. The experimental methods and reagents without specific conditions in the following examples are all carried out or configured according to conventional conditions or conditions recommended by the manufacturer.

[0040] Example 1

[0041] Catalyst preparation: 5.95 g Zn(NO 3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 23.05g of anhydrous citric acid were dissolved in 20mL of deionized water and stirred evenly. After being completely dissolved, the temperature was raised to 90°C and dried for 4h. The above product was then transferred to a muffle furnace and calcined at 400°C for 6h. It was sieved to 40-60 mesh. The obtained catalyst was named ZnFe 2 O 4 , XRD spectrum see Figure 1 , TEM image see Figure 2 .

[0042] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 3, the reaction temperature is 300°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 18000mL / g cat / h. The reaction results are shown in Table 1.

[0043] Example 2

[0044] Catalyst preparation: 5.95 g Zn(NO 3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 17.29 g of anhydrous citric acid were dissolved in 20 mL of deionized water and stirred evenly. According to the final loading amount of In being 2 wt %, 0.26 g In(NO 3 ) 3 After being completely dissolved, the temperature was raised to 100°C and dried for 4 hours. The obtained product was then transferred to a muffle furnace and calcined at 400°C for 4 hours. The product was sieved to 40-60 mesh. The obtained catalyst was named In-ZnFe 2 O 4 .

[0045] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 3, the reaction temperature is 330°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 20000mL / g cat / h. The reaction results are shown in Table 1.

[0046] Example 3

[0047] Preparation of catalyst: 4.39 g C 4 H 6 O 4 Zn·2H 2 O, 9.80g C 6 H 5 FeO 7 5.41 g of urea was dissolved in 20 mL of deionized water and stirred evenly. According to the final loading amount of Pd being 1 wt%, 0.97 g of palladium nitrate solution (Pd, 5 wt%) was added thereto. After being completely dissolved, the temperature was raised to 110 ° C and dried for 4 h. The obtained product was then transferred to a muffle furnace and calcined at 350 ° C for 6 h. It was sieved to 40-60 mesh. The obtained catalyst was named Pd-ZnFe 2 O 4 .

[0048] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 3, the reaction temperature is 280°C, the reaction pressure is 3MPa, and the reaction mass space velocity is 15000mL / g cat / h. The reaction results are shown in Table 1.

[0049] Example 4

[0050] Catalyst preparation: 2.73 g ZnCl 2 , 10.81 g FeCl 3 6H 2 O and 8.10g oxalic acid were dissolved in 20mL deionized water and stirred evenly. According to the final loading amount of Pt being 1wt%, 0.97g platinum nitrate solution (Pt, 5wt%) was added thereto. After being completely dissolved, the temperature was raised to 120°C and dried for 2h. The obtained product was then transferred to a muffle furnace and calcined at 350°C for 8h. It was sieved to 40-60 mesh. The obtained catalyst was named Pt-ZnFe 2 O 4 .

[0051] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 2, the reaction temperature is 290°C, the reaction pressure is 4 MPa, and the reaction mass space velocity is 2000 mL / g cat / h. The reaction results are shown in Table 1.

[0052] Example 5

[0053] Catalyst preparation: 5.95 g Zn(NO3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 30.81 g sucrose were dissolved in 20 mL deionized water and stirred evenly. According to the final loading amount of Cu being 5 wt %, 0.96 g Cu(NO 3 ) 2 ·3H 2 O, after being completely dissolved, the temperature was raised to 100°C and dried for 4 hours, and then the above product was transferred to a muffle furnace and calcined at 400°C for 6 hours, and sieved to 40-60 mesh. The obtained catalyst was named Cu-ZnFe 2 O 4 .

[0054] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 4, the reaction temperature is 300°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 15000mL / g cat / h. The reaction results are shown in Table 1.

[0055] Example 6

[0056] Catalyst preparation: 5.95 g Zn(NO 3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 8.10 g oxalic acid were dissolved in 20 mL deionized water and stirred evenly. According to the final loading amount of Cr being 2 wt %, 0.76 g Cr(NO 3 ) 3 9H 2 O, after being completely dissolved, the temperature was raised to 100 ° C and dried for 4 hours, and then the above product was transferred to a muffle furnace and calcined at 430 ° C for 6 hours, and sieved to 40-60 mesh. The obtained catalyst was named Cr-ZnFe 2 O 4 .

[0057] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 3, the reaction temperature is 340°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 20000mL / g cat / h. The reaction results are shown in Table 1.

[0058] Example 7

[0059] Catalyst preparation: 5.95 g Zn(NO 3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 30.81 g sucrose were dissolved in 20 mL deionized water and stirred evenly. According to the final loading amount of Ga being 3 wt %, 0.55 g Ga(NO 3 ) 3 ·xH 2 After the mixture is completely dissolved, the temperature is raised to 100°C and dried for 4 hours. The obtained product is then transferred to a muffle furnace and calcined at 400°C for 6 hours. The product is sieved to 40-60 mesh. The obtained catalyst is named Ga-ZnFe 2 O 4 .

[0060] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2 The molar ratio is 3, the reaction temperature is 310°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 9000mL / g cat / h. The reaction results are shown in Table 1.

[0061] Example 8

[0062] Catalyst preparation: 5.95 g Zn(NO 3 ) 2 6H 2 O, 16.16 g Fe(NO 3 ) 3 9H 2 O and 11.53 g of anhydrous citric acid were dissolved in 20 mL of deionized water and stirred evenly. According to the final loading amount of Zr being 4 wt %, 0.51 g of ZrO(NO 3 ) 2 ·xH 2 After the mixture is completely dissolved, the temperature is raised to 100°C and dried for 4 hours. The obtained product is then transferred to a muffle furnace and calcined at 400°C for 6 hours. The product is sieved to 40-60 mesh. The obtained catalyst is named Zr-ZnFe 2 O 4 .

[0063] 1.00 g of the above catalyst was loaded into a fixed bed reactor, and the reaction conditions were: H 2 With CO 2The molar ratio is 3, the reaction temperature is 320°C, the reaction pressure is 5MPa, and the reaction mass space velocity is 9000mL / g cat / h. The reaction results are shown in Table 1.

[0064] Table 1

[0065]

[0066] The above examples are for the purpose of illustrating the embodiments disclosed by the present invention and are not to be construed as limitations of the present invention. In addition, the various modifications listed herein and the variations of methods and compositions in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been specifically described in conjunction with various specific preferred embodiments of the present invention, it should be understood that the present invention should not be limited to these specific embodiments. In fact, various modifications obvious to those skilled in the art as described above to obtain the invention should be included within the scope of the present invention.

Claims

1. Use of a catalyst in the synthesis of methanol by hydrogenation of carbon dioxide, characterized in that: The general formula of the catalyst is x M-ZnFe2O4, M element is In or Pd, the content of M element x The range of is 1~2wt%, and the catalyst has a spinel structure.

2. Use of the catalyst according to claim 1 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The catalyst is nanoparticles with an average particle size of 10-15 nm.

3. Use of the catalyst according to claim 1 or 2 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The preparation method of the catalyst comprises drying and calcining a mixed solution including zinc salt, iron salt, salt of M element, organic solute and water to obtain the catalyst; the organic solute is selected from at least one of urea, citric acid, oxalic acid and sucrose.

4. Use of the catalyst according to claim 3 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The zinc salt is selected from at least one of zinc nitrate, zinc acetate and zinc chloride; And / or, the iron salt is selected from at least one of ferric nitrate, ferric chloride and ferric citrate; And / or, the salt of element M is selected from at least one of nitrate of element M and chloride of element M.

5. Use of the catalyst according to claim 3 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The molar ratio of the zinc salt, the iron salt and the organic solute is 1:2:3-6; and / or, the drying temperature is 80-120°C; and / or, the drying time is 2 to 4 hours; And / or, the calcination temperature is 350-430°C; And / or, the calcination time is 4 to 8 hours.

6. Use of the catalyst according to claim 1 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The raw gas containing CO2 and H2 reacts under the catalyst conditions to obtain methanol.

7. Use of the catalyst according to claim 6 in synthesizing methanol by hydrogenation of carbon dioxide, characterized in that: The molar ratio of H2 to CO2 is 2 to 4; And / or, the mass space velocity of the reaction is 2000~20000 mL / g cat / h; and / or, the reaction pressure is 3-5 MPa; And / or, the reaction temperature is 280-340°C; And / or, the reaction is carried out in a fixed bed reactor.

Citation Information

Patent Citations

  • Carbon dioxide hydrogenation catalyst and preparation method and application thereof

    CN113145113A

  • Preparation method and application of ZnFe2O4-based catalyst

    CN114950448A